Clinical, histological, and molecular differences in melanoma due to different TERT promoter mutations subtypes.: A retrospective cross-sectional study in 684 melanoma patients - Manrique-Silva, Esperanza; David, Millán-Esteban; Maider, Aguerralde-Martin; García-Casado, Zaida; Moro, Ruggero; Requena, Celia; Través, Victor; Virós, Amaya; Kumar, Rajiv; Nagore, Eduardo (Pigment cell & melanoma research, 2024)
Differences in survival according to the pTERT mutation subtypes (−124C > T, −146C > T, and tandem −138_139CC > TT) have been observed. The present study aimed to describe the clinical as the histopathological and molecular cutaneous melanoma features according to the presence of the three most prevalent pTERT mutation subtypes (−124C > T, −146C > T, and tandem −138_139CC > TT). A retrospective cross-sectional study including 684 patients was designed, and a Partial Least-Squares Discriminant Analysis (PLS-DA) was performed. After the PSL-DA, it was observed that the tandem −138_139CC > TT subtype differs from the other subtypes. The model demonstrated that the −124C > T and the −138_139 CC > TT subtypes were associated with fast-growing melanomas (OR 0.5, CI 0.29-0.86, p = .012) and with Breslow >2 mm (OR 0.6, CI 0.37-0.97, p = .037), compared to the −146C > T mutation. Finally, the −124C > T appeared to be more associated with the presence of TILs (non-brisk) than the −146C > T (OR 0.6, CI 0.40-1.01, p = .05). These findings confirmed that the −124C > T and the tandem −138_139 CC > TT subtypes are both highly associated with the presence of features of aggressiveness; however, only the −124C > T was highly associated with TILs. This difference could explain the worse survival rate associated with the tandem −138_139CC > TT mutations.